PRED(TAP): a system for prediction of peptide binding to the human transporter associated with antigen processing - Zhang, Guang Lan (BioMed Central, 2006)
BACKGROUND: The transporter associated with antigen processing (TAP) is a critical component of the major histocompatibility complex (MHC) class I antigen processing and presentation pathway. TAP transports antigenic peptides into the endoplasmic reticulum where it loads them into the binding groove of MHC class I molecules. Because peptides must first be transported by TAP in order to be presented on MHC class I, TAP binding preferences should impact significantly on T-cell epitope selection. DESCRIPTION: PRED(TAP )is a computational system that predicts peptide binding to human TAP. It uses artificial neural networks and hidden Markov models as predictive engines. Extensive testing was performed to valid the prediction models. The results showed that PRED(TAP )was both sensitive and specific and had good predictive ability (area under the receiver operating characteristic curve Aroc>0.85). CONCLUSION: PRED(TAP )can be integrated with prediction systems for MHC class I binding peptides for improved performance of in silico prediction of T-cell epitopes. PRED(TAP )is available for public use at [1].